Solvent-free, highly efficient one-pot multi-component synthesis of 1-amido- and 1-carbamato-alkyl naphthols/phenols catalyzed by ethylammonium nitrate as reusable ionic liquid under neat reaction condition at ambient temperature - Mulla, Shafeek Abdul Rashid; Salama, Tarek A.; Pathan, Mohsinkhan Y.; Inamdar, Suleman M.; Chavan, Santosh S. (Tetrahedron Letters, 2013)
A solvent-free, environmentally clean, mild, and simple one-pot multi-component protocol has been developed for the efficient synthesis of 1-amido- and 1-carbamato-alkyl naphthols/phenols in excellent yields via one-pot three-component condensation of various aldehydes, amides/carbamates/urea, and naphthols/phenols using ethylammonium nitrate (EAN) as a reusable ionic liquid catalyst under neat reaction condition at ambient temperature. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; amide; Carbamate Phenol; Ethylammonium nitrate (EAN); Urea

Synthesis of annulated bis-indoles through Au(I)/brønsted acid-catalyzed reactions of (1H-indol-3-yl)(aryl)methanols with 2-(arylethynyl)-1H-indoles - Patil, Nitin T.; Inamdar, Suleman M.; Gonnade, Rajesh Ghanshyam (Organic & Biomolecular Chemistry, 2017)
A general method to access annulated bis-indoles from (1H-indol-3-yl)(aryl)methanols and 2-(arylethynyl)-1H-indoles under the catalysis of the Ph3PAuOTf/Brønsted acid binary catalyst system has been developed. The reaction was found to proceed in a highly efficient manner and benefit from easy-to-make starting materials, broad substrate scope and operational simplicity. The potential of this method has also been exemplified for the synthesis of pyrrole-annulated indoles using 2-(phenylethynyl)-1H-indoles and phenyl(1H-pyrrol-2-yl)methanols. Furthermore, the use of a ternary catalyst system, involving PdCl2/Brønsted acid/Ph3PAuOTf catalysts, has been realized for the synthesis of annulated bis-indoles starting directly from 2-(phenylbuta-1,3-diyn-1-yl)aniline and (1H-indol-3-yl)(aryl)methanol. Mechanistically, this reaction is very interesting since the overall process involves three different catalytic cycles catalyzed by three different catalysts in a relay fashion.